Penerapan Metode Item Base Collaborative Filtering Berbasis Web Pada Recommender System Laptop: Application of the Web-Based Item Base Collaborative Filtering Method on Laptop Recommender Systems - Detri Amelia Chandra; Firman Santosa; Sri Wahyudi (YCMM, 2021)
Computers are one form of information technology development whose number of uses is always increasing to meet people's work needs. From this, a type of computer that can be carried anywhere, such as a laptop, was created. A laptop is a portable computer that is relatively medium and light in size and has a power source from a battery or A/C adapter, which can be used to turn on and recharge the laptop. Nowadays there are many various brands, types, specifications and functions of laptops that are sold in the market at varying prices, consumers often find it difficult to choose a laptop that suits their needs. Not infrequently consumers choose laptops with high specifications and expensive prices but are not used for supporting activities such as graphic design, video editing, animation and programming but are more often used for activities that do not require high laptop specifications such as watching movies. Therefore we need a Recommender System with an item based collaborative filtering method that provides laptop recommendations that suit consumer needs.